2018
DOI: 10.1021/acs.orglett.8b02259
|View full text |Cite
|
Sign up to set email alerts
|

Eucalyptusdimers A–C, Dimeric Phloroglucinol–Phellandrene Meroterpenoids from Eucalyptus robusta

Abstract: Eucalyptusdimers A-C, three dimeric phellandrene-derived meroterpenoids featuring an unprecedented, fused skeleton between two phellandrene and two acylphloroglucinol subunits, along with one biogenetically related intermediate, (±)-eucalyprobusone A, were isolated from the fruits of Eucalyptus robusta. Their structures and absolute configurations were elucidated using spectroscopic data, X-ray crystallography, and electronic circular dichroism analysis. The isolated meroterpenoids were evaluated for their ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…(Table 4). Taking their structural characteristics and AChE inhibitory data into consideration, the observable structure-activity relationships can be summarized as follows (i) both FPMs featuring with a dihydropyran ring and acylphloroglucinol monomer were inactive; (ii) acylphloroglucinol dimers that be connected via an isopentyl moiety showed stronger AChE inhibitory effects than Rhodomyrtus tomentosa [35], the current findings indicated that FPM and acylphloroglucinol heterodimers [10] connected only by an isopentyl unit are more likely to be AChE inhibitors.…”
Section: Structural Elucidationmentioning
confidence: 79%
See 2 more Smart Citations
“…(Table 4). Taking their structural characteristics and AChE inhibitory data into consideration, the observable structure-activity relationships can be summarized as follows (i) both FPMs featuring with a dihydropyran ring and acylphloroglucinol monomer were inactive; (ii) acylphloroglucinol dimers that be connected via an isopentyl moiety showed stronger AChE inhibitory effects than Rhodomyrtus tomentosa [35], the current findings indicated that FPM and acylphloroglucinol heterodimers [10] connected only by an isopentyl unit are more likely to be AChE inhibitors.…”
Section: Structural Elucidationmentioning
confidence: 79%
“…Plants of Eucalyptus genus (Myrtaceae) are a prolific resource of phloroglucinol derivatives, especially formylated phloroglucinol meroterpenoids (FPMs) [1][2][3][4]. These Eucalyptus secondary metabolites not only possess multifarious bioactive properties, including protein tyrosine phosphatase 1B inhibitory [2], immunosuppressive [3], antimicrobial [4,5], antiviral [6], anticancer [7][8][9], AChE inhibitory [10], and anti-leishmanial [11] effects, but also have attracted significant attention from the synthetic organic chemistry community [12][13][14][15][16][17][18]. Eucalyptus robusta, a tall arbor indigenous to Australia, is widely cultivated in south China.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These natural products have also attracted considerable interests from our research group. [7][8][9] As part of our continuing efforts to search for structurally intriguing and bioactive molecules from Myrtaceae family, three new polymethylated phloroglucinol meroterpenoids (PPMs), named rhotomentodiones CÀ E (Figure 1), were obtained from the twigs and leaves of Rhodomyrtus tomentosa. All these isolates were evaluated for their antibacterial and AChE inhibitory activities.…”
Section: Introductionmentioning
confidence: 99%
“…Further unusual natural products whose structures have been confirmed by X-ray analyses include cleistoperlones A 7 and C 8, from Cleistocalyx operculatus, 7 and eucalyptusdimer A 9, from Eucalyptus robusta. 8 Cleistoperlone A 7 is formed from two cinnamylphloroglucinol units and cleistoperlone C 8, from a cinnamylphloroglucinol unit with α-pinene. Three homologous cytochrome P450 enzymes from three indole alkaloid-producing plants have been discovered and shown to allow entry to two distinct classes of alkaloids, the sarpagans (e.g.…”
mentioning
confidence: 99%